Effects of systemic erythropoietin on ischemic wound healing in rats - (:unkn) unknown (My University, 2015)
Results of in vivo studies have shown erythropoietin (EPO) is associated with anti-inflammatory, anti-apoptotic, and cell protective effects on wound healing. These effects are dose-dependent. The aim of this study was to evaluate whether the duration of EPO treatment affects the healing process in the ischemic wound. Forty-two (42) Sprague-Dawley rats were anesthetized, wounded with H-shaped flaps, and randomized to 2 groups; Group 1 received 400 u/kg/day EPO and Group 2 received a saline solution, both via intraperitoneal injection following the wounding. All substances were administered once daily at the same time for up to 10 days after surgery. At days 3, 5, and 10, 7 rats from each group were sacrificed. Skin samples were stained with hematoxylin/eosin, viewed under an optical microscope at 10X and 40X magnification, and analyzed by blinded investigators for re-epithelialization, neovascularization amount and maturation of granulation tissue, inflammatory cells, and ulcer healing using an evaluation scale where 0 = none; 1 = partial; 2 = complete, but immature/thin: and 4 = complete and mature. Blood hemoglobin and hematocrit levels also were measured. Data were analyzed using ANOVA one-way test (P <0.05). Hemoglobin and hematocrit levels rose while subsequent doses of EPO were administered over time, accompanied by a transient surge in healing on day 5, when differences in healing scores were significant. Flap necrosis, ulceration, and abscess were noted on post-wounding day 10 near the pedicle. The study showed EPO therapy can improve wound healing early in the post-wounding period but can reduce wound healing after post-injury treatment day 5. Further research is necessary, particularly to establish how EPO influences the microcirculation and rheology.
Keywords: Animals; Rats; Surgical Flaps; Wound Healing; Rats, Sprague-Dawley; Anti-Inflammatory Agents; Necrosis; Ischemia; Hematocrit; Hemoglobins; Erythropoietin; Microcirculation